A numerical study on the effects of inclination angle and container material on thermal energy storage by phase change material in a thick-walled disc - Kiyak, Burak; Öztop, Hakan Fehmi Fehmi; Aksoy, Ishak Gokhan (Emerald Group Publishing Ltd, 2024)
PurposeThe purpose of this study is to examine the effects of inclination angle on the thermal energy storage capability of a phase change material (PCM) within a disc-shaped container. Different container materials are also tested such as plexiglass and aluminium. This study aims to assess the energy storage capacity, melting behaviour and temperature distributions of PCM with a specific melting range (22 degrees C-26 degrees C) for various governing parameters such as inclination angles, aspect ratios (AR) and temperature differences (Delta T) and compare the melting behaviour and energy storage performance of PCM in aluminium containers to those in plexiglass containers.Design/methodology/approachA finite volume approach was adopted to evaluate the thermal energy storage capability of PCMs. Five inclination angles ranging from 0 degrees to 180 degrees were considered and the energy storage capacity. Also, the melting behaviour of the PCM and temperature distributions of the container with different materials were tested. Two different AR and Delta T values were chosen as parameters to analyse for their effects on the melting performance of the PCM. Conjugate heat transfer problem is solved to see the effects of conduction mode of heat transfer.FindingsThe results of the study indicate that as AR decreases, the effect of the inclination angles on the energy storage capacity of the PCM decreases. For lower Delta T, the difference between the maximum and minimum stored energies was 20.88% for AR = 0.20, whereas it was 6.85% for AR = 0.15. Furthermore, under the same conditions, the PCM stored 8.02% more energy in plexiglass containers than in aluminium containers.Originality/valueThis study contributes to the understanding of the influence of inclination angle, container material, AR and Delta T on the thermal energy storage capabilities of PCM in a novel designed container. The findings highlight the importance of AR in mitigating the effect of the inclination angle on energy storage capacity. Additionally, comparing aluminium and plexiglass containers provides insights into the effect of container material on the melting behaviour and energy storage properties of PCM.
Keywords: Energy storage; Phase change material; Melting; Disc-shaped container; Aspect ratio